Macro and microcontextual taboo words in Iranian pre and post revolution movies / Zahra Samadi - Samadi, Zahra (2014)
Taboo words are the inseparable parts of language. It has been proved that this phenomenon exists in all languages including Farsi. Taboo words change over time. Some words, which were considered once taboo in the past, do not carry any “tabooness” at present. Hence, in an attempt to investigate the changes of taboo words/expressions in Farsi language, a research was conducted. This study compares the taboo words used by characters in movies. These characters portray lower class and middle class members of Iranian society. Two Iranian movies produced before and after the revolution (1979) in Iran are chosen to conduct this study. The data source of the taboo words come from “Qeisar” and “The Separation”. To answer the research questions and analyze the data, Hongxu and Guisen‟s (1990) framework for taboo words is used. According to this classification, the researcher first categorizes the used taboo words/expressions into seven (7) tabooed subjects. The study also investigates the factors which have influenced the formation of those taboo words among lower class and middle class members of Iranian society including macrocontexul (societal) factors and mircontexual (situational) factors. This study shows how the concept of tabooness and the factors that led to taboo formation have changed over time.